Effective Communication in Building Healthy and Productive Relationships - Soid; Muhammad Fatih; Nanang Fauzi; Efrita Norman (MES Management Journal, 2025)
Effective communication plays a crucial role in fostering healthy and productive relationships, both in personal and professional contexts. Miscommunication or lack of clear interaction often leads to misunderstandings, conflict, and reduced collaboration. This study investigates the impact of effective communication strategies on relationship quality and productivity, with the aim of identifying key elements that enhance interaction and understanding. Employing a mixed-methods approach, the research integrates quantitative surveys to measure communication effectiveness and qualitative interviews to gain deeper insights into participants’ experiences. The study was conducted across diverse settings, including workplaces and interpersonal relationships, ensuring a comprehensive analysis of the phenomenon. The findings highlight that clarity, active listening, empathy, and feedback are critical components in effective communication. Participants who engaged in these practices reported improved trust, reduced conflicts, and enhanced collaborative outcomes. Additionally, the results suggest that communication training significantly enhances these skills, leading to better relational and organizational performance. This research concludes that effective communication is not only pivotal in resolving conflicts and fostering harmony but also in driving productivity and goal achievement. By providing evidence-based strategies and emphasizing the importance of communication in building relationships, this study contributes to the field by offering practical frameworks for individuals and organizations to enhance their interaction dynamics. The insights gained underline the transformative potential of effective communication, paving the way for more harmonious and efficient social and professional environments.